2001
DOI: 10.1038/sj.leu.2402216
|View full text |Cite
|
Sign up to set email alerts
|

Cladribine combined with cyclophosphamide and mitoxantrone as front-line therapy in chronic lymphocytic leukemia

Abstract: The objective of the study was to determine the effectiveness and the toxicity of a combined chemotherapy consisting of cladribine (2-CdA), mitoxantrone and cyclophosphamide (CMC regimen) in the treatment of previously untreated B cell chronic lymphocytic leukemia (B-CLL). From August 1998 to December 2000 2-CdA was administered at a dosage of 0.12 mg/kg for 3 (CMC3) or 5 (CMC5) consecutive days, mitoxantrone at 10 mg/m 2 on day 1 and cyclophosphamide at 650 mg/m 2 on day 1 to 62 patients with advanced or prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 33 publications
(49 reference statements)
0
19
0
1
Order By: Relevance
“…The doses and schedule of treatment were based on previous studies in CLL or low-grade lymphoma patients, performed earlier by our group. 11,16,17 Regarding CMC, 3-day protocol was selected for this study based on our previous results. 17 We showed that a 3-day schedule (previously referenced as CMC3) has similar efficacy and lower toxicity than a 5-day CMC (CMC5).…”
Section: Randomization Procedures and Treatment Modalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The doses and schedule of treatment were based on previous studies in CLL or low-grade lymphoma patients, performed earlier by our group. 11,16,17 Regarding CMC, 3-day protocol was selected for this study based on our previous results. 17 We showed that a 3-day schedule (previously referenced as CMC3) has similar efficacy and lower toxicity than a 5-day CMC (CMC5).…”
Section: Randomization Procedures and Treatment Modalitymentioning
confidence: 99%
“…In our previous phase 2 studies, we showed that combined treatment with 2-CdA and CY (CC regimen) or with 2-CdA, CY, and MIT (CMC regimen) gave high ORRs and CRs and acceptable toxicity in previously untreated patients with CLL. 16,17 In this report, we present the results of a prospective, randomized multicenter trial comparing the efficacy and toxicity of CC and CMC combination regimens to 2-CdA alone.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Despite the fact that CLL is an incurable hematologic malignancy, complete remission can be achieved with conventional chemotherapy. [14][15][16][17][18][19] In 1996, The National Cancer Institute-sponsored Working Group (NCI-WG) on CLL defined patients with complete remission (CR) and persistent bone marrow nodules as nPR. 20 The main goal of this study is to investigate the significance of the levels of the lymphoid infiltrate in nPR CLL patients and its correlation with clinical progression and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…56,[93][94][95][96] Combined treatment with NA, mitoxantrone and CY has been undertaken both in previously treated and untreated patients with B-CLL. 93,97,98 However, the efficacy of these regimens seem to be similar to that observed after treatment with FAMP or 2-CdA alone. In addition, the toxicity, especially myelosuppression and infections of such combined therapy is high and reduction of NA doses is essential.…”
Section: Nucleoside Analogues In Combination With Other Agentsmentioning
confidence: 63%